SOSIALIASASI PENCEGAHAN HOAX SEPUTAR INFORMASI COVID 19 DI KALANGAN REMAJA - Windhi Tia Saputra; Ratu Nadya W; Ratu Laura M.B.P (Program studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Persada Indonesia YAI, 2021)
It has been more than a year since the Covid-19 virus was first discovered and spread around the world. The pandemic started in the city of Wuhan, China and has claimed many lives and tremendous effect of terror to people around the world. Because of the increasing of the pandemic, the Indonesian government as well as the rest of the world are taking steps to reduce and stop the spread of this deadly virus. Experts in the health sector are also moving quickly to observe the virus and find ways to eliminate this pandemic. In the midst of the activeness of health experts and the government in fighting this virus, various health information emerged to prevent and even kill the corona virus. However, not all of the information is true and we called them hoax. The spread of various hoax information during the pandemic is very massive. There are 1,387 hoax issues on various digital platforms. One of the effort to reduce hoax is provide counseling about hoax information. This Community Service activity is carried out in junior high school to increase youth's knowledge about the world of hoax and how to avoid them.